Efektivitas Pembelajaran Game Based Learning Berbantuan Wordwall Terhadap Peningkatan Hasil Belajar Materi Operasi Hitung Campuran - Febriyanti, Syifa; Purhanudin, MS Viktor; Anwar, Choirul (Jurnal keilmuan dan Kependidikan dasar, 2025)
This study was motivated by the low learning outcomes of mixed arithmetic operation material in madrasah ibtidaiyah due to monotonous conventional methods. The research aims to test the effectiveness of the Game Based Learning (GBL) model assisted by Wordwall media on improving learning outcomes of third grade students at MIS Perwanida Salatiga. The method used was a quasi-experiment (Pretest-Posttest Control Group Design) with a sample of 31 students (16 experimental group, 15 control group). The research instrument consists of questions that have been pilot-tested and declared valid and reliable. The test results were analyzed using the N-Gain test and independent samples t-test through IBM SPSS Statistics 25. The results showed: (1) The improvement in learning outcomes of the experimental group was significant (N-Gain 0.8545 / high category), far exceeding the control group (N-Gain 0.5735 / medium category); (2) The average posttest of the experimental group (91.25) was statistically superior to the control group (72.67) with a p-value of 0.000 (<0.05). The conclusion of the study proves that the GBL model assisted by Wordwall is effective in significantly improving student learning outcomes. The findings recommend the integration of game-based technology in basic math learning to create interactive and meaningful learning experiences.